Adherence to the new policy framework of the World Cancer Research Fund International in developing a policy package for the prevention of gastrointestinal cancers in Iran: a Delphi study. Issue 1 (1st January 2021) - Janati, Ali; Khodayari-zarnaq, Rahim; Khanijahani, Ahmad; Khoshbaten, Manouchehr; Ghamkhar, Alireza; Kabiri, Neda
ABSTRACT: Background: Gastrointestinal cancers in Iran are among the major non-communicable diseases with a considerable burden on the health system. Changes in lifestyles as well as environmental factors have resulted in the emergence of these cancers. Objective: To elicit and quantitatively verify experts' opinions regarding the potential public health impact, feasibility, economic impact, and budgetary impact of gastrointestinal cancer prevention policies in Iran. Methods: Sixteen experts from Iran were recruited in an email-based, two-round Delphi study. In each round, a questionnaire of policy options for preventing gastrointestinal cancers, which adhered to the new policy framework of the World Cancer Research Fund International, was given to participants. In the first round, experts were asked to provide opinions for and against the policy options. The second round evaluated the policy options for their public health impact, feasibility, economic impact, and budgetary impact. Results: A total of 32 policy options were organized based on three domains: health-enhancing environments, system changes, and behavior change communications. Of the 32 policy options, there were consensus in 31 (96%) and 30 (93%) options for public health impact and feasibility, respectively. On study completion, experts reached a consensus in 29 of 32 (90%) policy options for economic impact; only on 26 (81%) of these policy options did participants reached consensus for budgetary impact. Conclusion: Findings indicated that although nearly all policy options reached a consensus for their public health impact, some options are not feasible or do not appear to have an economic rationale for being implemented. Moreover, it is crucial to take into account the inter-sectoral collaboration between health and non-health sectors. Findings from this study can be helpful for health policymakers in identifying support for evidence-informed approaches regarding gastrointestinal cancer prevention.